Membrane electrode assembly

By using a crown ether compound to form inclusion compounds with cerium or manganese ions, the membrane electrode assembly in polymer electrolyte fuel cells addresses durability issues, enhancing radical quenching and reducing ion segregation for improved longevity.

JP2025007966AInactive Publication Date: 2025-01-20TOYOTA JIDOSHA KK
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023109733
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing membrane electrode assemblies in polymer electrolyte fuel cells suffer from durability issues due to the segregation and movement of cerium ions, leading to areas with low concentration and subsequent deterioration of the electrolyte and catalyst layers.

Method used

Incorporating a crown ether compound containing an amino group or its salt as a host compound to form inclusion compounds with cerium or manganese ions, which act as radical quenching agents, thereby suppressing ion movement and concentration deviations, enhancing durability.

Benefits of technology

The membrane electrode assembly exhibits improved durability by effectively capturing hydrogen peroxide radicals, reducing deterioration, and maintaining performance over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007966000002
    Figure 2025007966000002
  • Figure 2025007966000001
    Figure 2025007966000001
Patent Text Reader

Abstract

To provide a membrane electrode assembly that is highly durable.SOLUTION: A membrane electrode assembly according to an embodiment includes a solid polymer electrolyte membrane, an anode catalyst layer disposed on one surface of the solid polymer electrolyte membrane, and a cathode catalyst layer disposed on the other surface of the solid polymer electrolyte membrane, and the membrane electrode assembly contains a metal ion selected from a cerium ion and a manganese ion, and a host compound capable of forming an inclusion compound with the metal ion, the host compound is a crown ether compound containing an amino group or a salt thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a membrane electrode assembly. [Background technology]

[0002] A solid polymer electrolyte fuel cell generally comprises a membrane electrode assembly (also referred to as "MEA") having a solid polymer electrolyte membrane as an electrolyte membrane, an anode catalyst layer disposed on one side of the solid polymer electrolyte membrane, and a cathode catalyst layer disposed on the other side of the solid polymer electrolyte membrane. The anode catalyst layer functions as a fuel electrode, and the cathode catalyst layer functions as an air electrode. Gas diffusion layers may also be disposed on both sides of the MEA, and this configuration is called a membrane electrode gas diffusion layer assembly (also referred to as "MEGA").

[0003] In a polymer electrolyte fuel cell, hydrogen peroxide (H2O2) may be generated from water and oxygen in the catalyst layer during power generation, and hydroxyl radicals (·OH) may be generated from hydrogen peroxide. These hydrogen peroxide and hydroxyl radicals can cause deterioration of the polymer electrolyte membrane and electrolyte resins such as ionomers contained in the catalyst layer.

[0004] Therefore, a technology has been proposed to render the hydrogen peroxide radicals generated during power generation in a fuel cell harmless by incorporating a radical quenching agent such as cerium ions into the MEA. The rendering of hydrogen peroxide radicals harmless is, for example, the reaction of hydrogen peroxide radicals into water.

[0005] For example, Patent Document 1 discloses a solid polymer electrolyte membrane made of a polymer electrolyte having a sulfonic acid group, which includes any one of the following (a) to (c): (a) cerium ions and an organic compound (X) capable of forming an inclusion compound with the cerium ions, (b) an inclusion compound (Y) made of the organic compound (X) in which the cerium ions are inclusions, and (c) at least one of the cerium ions and the organic compound (X) and the inclusion compound (Y). Patent Document 1 describes that the solid polymer electrolyte membrane of Patent Document 1 has excellent resistance to hydrogen peroxide or peroxide radicals. Although the reason is not clear, it describes that by including cerium ions and an organic compound (X) in the electrolyte membrane, at least a part of them forms an inclusion compound, which interacts with the sulfonic acid group (-SO3-), and a part of the sulfonic acid group is ion-exchanged with the inclusion compound (Y) to form a predetermined structure, thereby effectively improving the hydrogen peroxide or peroxide radical resistance of the polymer electrolyte membrane. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2008-130460 A Summary of the Invention [Problem to be solved by the invention]

[0007] As mentioned above, Patent Document 1 discloses a polymer electrolyte membrane or an anode catalyst layer containing cerium ions and 18-crown-6-ether as a radical quenching agent.

[0008] However, when a membrane electrode assembly containing cerium ions and 18-crown-6-ether was investigated, it was found that its performance deteriorated during use, and that there was room for improvement in terms of durability.

[0009] Therefore, an object of the present disclosure is to provide a membrane electrode assembly having excellent durability. [Means for solving the problem]

[0010] The present inventors have conducted intensive research to solve the above problems and have found that one of the reasons for the above performance degradation is that cerium ions move and segregate in the electrode during use, resulting in the generation of low concentration areas of cerium ions. As a result of further research, the present inventors have found that durability can be improved by using a crown ether compound or a salt thereof containing an amino group, and have arrived at the present disclosure.

[0011] Thus, an example of this embodiment is as follows. (1) A membrane electrode assembly having a solid polymer electrolyte membrane, an anode catalyst layer disposed on one surface of the solid polymer electrolyte membrane, and a cathode catalyst layer disposed on the other surface of the solid polymer electrolyte membrane, the membrane electrode assembly includes a metal ion selected from a cerium ion and a manganese ion, and a host compound capable of forming an inclusion compound with the metal ion, The host compound is a crown ether compound containing an amino group or a salt thereof. (2) The membrane / electrode assembly according to (1), wherein the host compound is a crown ether compound having an aromatic ring or an aliphatic ring substituted with an amino group, or a salt thereof. (3) The membrane / electrode assembly according to (1) or (2), wherein the host compound is a crown ether compound having a repeating structure of a (-CH2-CH2-Y-) unit or a (-CH2-CH2-CH2-Y-) unit, or a salt thereof (Y is each independently at least one selected from -O-, -NH-, and -NR-, at least one Y is selected from -NH- and -NR-, R is each independently an alkyl group having 1 to 6 carbon atoms, and when two R are present, those R may be linked via a C1-C6 alkylene in which one or two carbon atoms may be substituted with an oxygen atom). (4) The membrane / electrode assembly according to any one of (1) to (3), wherein the host compound is a crown ether compound having a repeating structure of a (-CH2-CH2-Y-) unit or a (-CH2-CH2-CH2-Y-) unit, or a salt thereof (Y is each independently at least one selected from -O- and -NR-, at least one Y is selected from -NR-, R is each independently an alkyl group having 1 to 4 carbon atoms, and when two R are present, those R may be linked via a C1 to C6 alkylene in which one or two carbon atoms may be substituted with an oxygen atom). (5) The membrane / electrode assembly according to any one of (1) to (4), wherein the salt of the crown ether compound containing an amino group is a nitrate, a sulfate, a carbonate, an acetate, or a propionate. Effect of the Invention

[0012] According to the present disclosure, it is possible to provide a membrane electrode assembly having excellent durability. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view for explaining an example of the configuration of a membrane electrode assembly and a polymer electrolyte fuel cell according to an embodiment of the present invention, and is a cross-sectional view of a main part of a fuel cell 10 as an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present embodiment is a membrane electrode assembly having a solid polymer electrolyte membrane, an anode catalyst layer disposed on one surface of the solid polymer electrolyte membrane, and a cathode catalyst layer disposed on the other surface of the solid polymer electrolyte membrane, the membrane electrode assembly including a metal ion selected from a cerium ion and a manganese ion, and a host compound capable of forming an inclusion compound with the metal ion, the host compound being a crown ether compound containing an amino group or a salt thereof.

[0015] This embodiment can provide a membrane electrode assembly with excellent durability. In this embodiment, cerium ions and / or manganese ions, which function as a radical quenching agent, are added to the membrane electrode assembly (e.g., an anode catalyst layer or a solid polymer electrolyte membrane). The cerium ions and / or manganese ions can capture and detoxify hydrogen peroxide radicals, thereby suppressing deterioration of the membrane electrode assembly. In addition, by adding a host compound for the above metal ions to the membrane electrode assembly, the movement of the above metal ions can be suppressed, and the concentration bias in the surface direction can be reduced. In this case, by using a crown ether compound containing an amino group or a salt thereof as the host compound, the effect of suppressing the movement of metal ions can be further improved. Therefore, the membrane electrode assembly according to this embodiment can also have excellent durability.

[0016] The configuration of this embodiment will be described below.

[0017] The solid polymer electrolyte membrane prevents the flow of electrons and gases, and also allows the protons (H + ) from the anode-side catalyst layer to the cathode-side catalyst layer. As the solid polymer electrolyte membrane in this embodiment, an electrolyte membrane having proton conductivity known in the art can be used. As the solid polymer electrolyte membrane, for example, a membrane formed from a fluororesin having a sulfonic acid group (such as Nafion (manufactured by DuPont), Flemion (manufactured by AGC), and Aciplex (manufactured by Asahi Kasei)) can be used.

[0018] The thickness of the solid polymer electrolyte membrane is not particularly limited, but is, for example, 5 μm to 50 μm from the viewpoint of improving proton conductivity.

[0019] The cathode catalyst layer functions as an air electrode (oxygen electrode).

[0020] The cathode catalyst layer includes at least an electrode catalyst (also simply referred to as a "catalyst") and an electrolyte. The electrode catalyst is preferably a metal-supported catalyst. In the metal-supported catalyst, the metal catalyst is supported on a carrier.

[0021] The carrier can be any carrier known in the art, and is not particularly limited. Examples of the carrier include carbon materials such as carbon black, carbon nanotubes, and carbon nanofibers; carbon compounds such as silicon carbide, etc. The carrier may be used alone or in combination of two or more.

[0022] There are no particular limitations on the metal catalyst, so long as it exhibits catalytic activity in the reaction at the electrode. Air electrode (cathode): O2+4H + +4e - →2H2O Hydrogen electrode (anode): 2H2 → 4H + +4e -

[0023] The metal catalyst is not particularly limited, but for example, platinum, palladium, rhodium, gold, silver, osmium, iridium, or an alloy of two or more of these can be used. The platinum alloy is not particularly limited, but for example, an alloy of platinum and at least one of aluminum, chromium, manganese, iron, cobalt, nickel, gallium, zirconium, molybdenum, ruthenium, rhodium, palladium, vanadium, tungsten, rhenium, osmium, iridium, titanium, and lead can be used. The metal catalyst may be used alone or in combination of two or more.

[0024] The content of the electrode catalyst in the cathode catalyst layer is not particularly limited, but is, for example, 3 to 40 mass % relative to the total mass of the catalyst layer.

[0025] The electrolyte used in the cathode catalyst layer is preferably an ionomer having a sulfonic acid group. Ionomers are also called cation exchange resins, and exist as clusters formed from ionomer molecules. The ionomer is not particularly limited, and for example, ionomers known in the art can be used. Examples of ionomers include fluororesin-based electrolytes such as perfluorosulfonic acid resins; sulfonated plastic electrolytes such as sulfonated polyether ketones, sulfonated polyether sulfones, sulfonated polyether ether sulfones, sulfonated polysulfones, sulfonated polysulfides, and sulfonated polyphenylenes; and sulfoalkylated plastic electrolytes such as sulfoalkylated polyether ether ketones, sulfoalkylated polyether sulfones, sulfoalkylated polyether ether sulfones, sulfoalkylated polysulfones, sulfoalkylated polysulfides, and sulfoalkylated polyphenylenes. The electrolyte may be used alone or in combination of two or more.

[0026] The anode catalyst layer functions as a fuel electrode, that is, a hydrogen electrode.

[0027] The anode catalyst layer includes an electrode catalyst and an ionomer. The ionomer is preferably an ionomer having a sulfonic acid group. Examples of the ionomer having a sulfonic acid group include those described above. In one embodiment, the anode catalyst layer may include, in addition to the electrode catalyst and the ionomer, a metal ion selected from a cerium ion and a manganese ion, and a host compound capable of forming an inclusion compound with the metal ion.

[0028] The electrode catalyst is not particularly limited, but for example, the above-mentioned materials can be used.

[0029] The ionomer having a sulfonic acid group is not particularly limited, and examples thereof include polymer electrolyte resins having ion conductivity such as perfluorosulfonic acid ionomers. Specific examples of the ionomer having a sulfonic acid group include Nafion and Aquivion (Solvay).

[0030] The membrane electrode assembly according to the present embodiment includes a metal ion selected from cerium ion and manganese ion, and a host compound capable of forming an inclusion compound with the metal ion. The cerium ion and / or manganese ion function as a radical quenching agent and can capture and detoxify hydrogen peroxide radicals, thereby suppressing deterioration of the membrane electrode assembly. In addition, by adding a host compound for the metal ion to the membrane electrode assembly, the movement of the metal ion can be suppressed, and the concentration bias in the surface direction can be reduced.

[0031] The metal ions are selected from cerium ions and manganese ions. The cerium ions and manganese ions function as radical quenching agents. The radical quenching agent can facilitate the conversion of hydroxide radicals generated from hydrogen peroxide to hydroxide ions, and can suppress the deterioration of the anode catalyst layer. For example, the reaction of hydroxide radicals to hydroxide ions by cerium ions is as follows. Ce 3+ + OH (hydroxyl radical) → Ce 4+ +OH - (hydroxide ion)

[0032] The cerium ion may be either +3 or +4. The manganese ion may be either +3 or +4.

[0033] The cerium salt for obtaining cerium ions is not particularly limited, and examples thereof include cerium nitrate, cerium carbonate, cerium acetate, cerium chloride, cerium sulfate, diammonium cerium nitrate, and tetraammonium cerium sulfate. The cerium salt may be used alone or in combination of two or more. The cerium salt may be an organometallic complex salt. Examples of the organometallic complex salt include cerium acetylacetonate.

[0034] The manganese salt for obtaining manganese ions is not particularly limited, and examples thereof include manganese nitrate, manganese carbonate, manganese acetate, manganese chloride, manganese sulfate, etc. The manganese salt may be used alone or in combination of two or more kinds.

[0035] The host compound in this embodiment forms an inclusion compound with cerium ions or manganese ions as a guest compound. The inclusion compound refers to an addition compound in which the above-mentioned metal ions as a guest compound are included in the host compound. The host compound may be used alone or in combination of two or more.

[0036] The host compound in this embodiment is a crown ether compound containing an amino group or a salt thereof. The number of ring members of the host compound is preferably 15 or more, and more preferably 18 or more. The crown ether compound containing an amino group or a salt thereof easily donates electrons to metal ions such as cerium ions to form coordinate bonds, and as a result, it is possible to more effectively form an inclusion compound.

[0037] In the present specification, a crown ether compound is a compound having a cyclic structure having a repeating structure of a (-CH2-CH2-Y-) unit or a (-CH2-CH2-CH2-Y-) unit, and each Y is independently at least one selected from -O-, -NH- and -NR-. The crown ether compound can capture a metal ion in this cyclic structure to form an inclusion compound. The crown ether compound containing an amino group (including a primary amino group, a secondary amino group, and a tertiary amino group) may have an amino group in the cyclic structure (the above Y is -NH- or -NR-) or as a substituent. The amino group as a substituent is represented by -NR1R2, and R1 and R2 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0038] In one embodiment, the crown ether compound or its salt containing an amino group is a crown ether compound or its salt having an aromatic ring or an aliphatic ring with an amino group as a substituent (a crown ether compound or its salt having an aromatic ring or an aliphatic ring substituted with an amino group). The crown ether compound having an aromatic ring or an aliphatic ring with an amino group has the effect that the amino group donates electrons to metal ions such as cerium to form coordinate bonds, and also has high hydrophobicity due to the structure of the aromatic ring or the aliphatic ring, so that migration to other layers (e.g., cathode catalyst layer) is suppressed. Examples of crown ether compounds having an aromatic ring or an aliphatic ring include benzo-15-crown-5-ether, dibenzo-15-crown-5-ether, benzo-18-crown-6-ether, dibenzo-18-crown-6-ether, benzo-21-crown-7-ether, dibenzo-21-crown-7-ether, benzo-24-crown-8-ether, dibenzo-24-crown-8-ether, cyclohexano-18-crown-6-ether, cyclohexano-21-crown-7-ether, cyclohexano-24-crown-8-ether, dicyclohexano-18-crown-6-ether, dicyclohexano-21-crown-7-ether, dicyclohexano-24-crown-8-ether, and the like. Examples of crown ether compounds having an amino group include compounds in which the aromatic ring or aliphatic ring of these compounds is substituted with at least one amino group. The number of the substituents is, for example, 1 to 4, 1 to 3, 1 to 2, or 1. Specific examples of the crown ether compound containing an amino group include aminobenzo-15-crown-5-ether, aminobenzo-18-crown-6-ether, aminobenzo-21-crown-7-ether, and aminobenzo-24-crown-8-ether. These compounds may be used alone or in combination of two or more.

[0039] Examples of the salt of the crown ether compound containing an amino group include nitrates, sulfates, carbonates, acetates, and propionates. The salt may be used alone or in combination of two or more.

[0040] In one embodiment, the host compound is an ammonium salt of a crown ether compound having an aromatic ring or an aliphatic ring substituted with an amino group. By adding the host compound in the form of an ammonium salt to the catalyst ink, the interaction with the sulfonic acid group of the ionomer is reduced, and aggregation of the host compound and the ionomer in the catalyst ink can be prevented. As a result, productivity can be improved. Examples of acids that form ammonium salts include nitric acid, sulfuric acid, and carbonic acid.

[0041] In one embodiment, the crown ether compound or its salt containing an amino group is a crown ether compound or its salt having a repeating structure of a (-CH2-CH2-Y-) unit or a (-CH2-CH2-CH2-Y-) unit (Y is at least one selected from -O-, -NH- and -NR-, at least one Y is selected from -NH- and -NR-, R is each independently an alkyl group having 1 to 4 carbon atoms, and when two R are present, the R may be linked via a C1-C6 alkylene in which one or two carbon atoms may be substituted with an oxygen atom). An example of the "C1-C6 alkylene in which one or two carbon atoms may be substituted with an oxygen atom" linking two R is -O-(C1-C4 alkylene)-O-. The crown ether compound containing a secondary amino group (secondary amine) or a tertiary amino group (tertiary amine) in the cyclic structure can capture a metal ion in the cyclic structure to efficiently form an inclusion compound, thereby effectively suppressing the movement or segregation of the metal ion. Specific examples of the crown ether compound in this embodiment include 1-aza-15-crown-5-ether, 1-aza-1-methyl-15-crown-5-ether, 1-aza-18-crown-6-ether, 1-aza-1-methyl-18-crown-6-ether, 1-aza-21-crown-7-ether, 1-aza-1-methyl-21-crown-7-ether, 1-aza-24-crown-8-ether, 1-aza-1-methyl-24-crown-8-ether, Cryptand222, etc. As the salt, an ammonium salt is preferable. By adding the ammonium salt to the catalyst ink, the interaction with the sulfonic acid group of the ionomer is reduced, and the aggregation of the host compound and the ionomer in the catalyst ink can be suppressed, thereby improving productivity.

[0042] In one embodiment, the host compound is a crown ether compound having a repeating structure of a (-CH2-CH2-Y-) unit or a (-CH2-CH2-CH2-Y-) unit, or a salt thereof (Y is independently at least one selected from -O- and -NR-, at least one Y is selected from -NR-, R is independently an alkyl group having 1 to 4 carbon atoms, and when two R are present, the R may be linked via a C1 to C6 alkylene in which one or two carbon atoms may be substituted with an oxygen atom). A crown ether compound (tertiary amine compound) containing a tertiary amino group in a cyclic structure has a metal ion migration suppressing effect, and also has little interaction with the sulfonic acid group of the ionomer in the catalyst ink, so that the occurrence of aggregation of the host compound and the ionomer in the catalyst ink can be suppressed. As a result, the productivity can be improved.

[0043] In the membrane / electrode assembly of this embodiment, the host compound and at least a portion of the metal ions form an inclusion compound.

[0044] The host compound and metal ions can be contained in the anode catalyst layer, the solid polymer electrolyte membrane, or both.

[0045] When the anode catalyst layer contains a host compound and a metal ion, the anode catalyst layer contains at least an electrode catalyst, an electrolyte, a metal ion selected from a group consisting of a cerium ion and a manganese ion, and a combination of the metal ion and the host compound. The metal ion can facilitate conversion of a hydroxide radical generated from hydrogen peroxide to a hydroxide ion, thereby suppressing deterioration of the anode catalyst layer.

[0046] The content of the metal ion and the host compound in the anode catalyst layer is preferably 0.1 to 20 mass% based on the total solid content of the anode catalyst layer. In addition, regarding the content, the inclusion compound is regarded as a mixture of the metal ion and the host compound. That is, when the metal ion and the host compound are added to the anode catalyst layer separately or simply mixed, even if an inclusion compound is formed in the polymer electrolyte, the amount of the inclusion compound is not taken into consideration, and only the total amount of the mixed metal ion and the inclusion compound is subject to calculation. In addition, when an inclusion compound is formed in advance and then added to the anode catalyst layer, the amount of the inclusion compound is the total amount of the metal ion and the inclusion compound that formed the inclusion compound. Furthermore, in addition to the metal ion and the host compound that formed the inclusion compound, if there are metal ions and a host compound that do not form an inclusion compound, they are also subject to calculation.

[0047] Regarding the relative ratio of the metal ion to the host compound in this embodiment, the molar ratio of the host compound to the metal ion ([moles of host compound] / [moles of metal ion]) is, for example, 0.1 to 10, preferably 0.2 to 7.5, and preferably 0.4 to 5.0. That is, the content of the host compound is, for example, 0.1 to 10 mol, preferably 0.2 to 7.5 mol, and preferably 0.4 to 5.0 mol, per 1 mol of the metal ion. Note that, even in this relative ratio, the inclusion compound is regarded as a mixture of both, as in the above.

[0048] When the solid polymer electrolyte membrane contains a host compound and a metal ion, the solid polymer electrolyte membrane containing the host compound and the metal ion can be obtained, for example, by the following method. (1) A solid polymer electrolyte membrane is immersed in a solution containing metal ions to exchange groups such as sulfonic acid groups with metal ions, and then the membrane is immersed in a solution containing a host compound to incorporate the host compound into the membrane. (2) A method in which a compound containing metal ions (e.g., a cerium salt) is added to a dispersion of a polymer electrolyte to exchange groups such as sulfonic acid groups with metal ions, and then a solution or solid containing a host compound is added to the dispersion, and the resulting liquid is used for coating to form a film. (3) A method in which a compound containing a metal ion (e.g., a cerium salt) is reacted with a host compound in a solvent to form an inclusion compound, and then a solid polymer electrolyte membrane is immersed in a solution in which the inclusion compound is dissolved in a solvent to ion-exchange groups such as sulfonic acid groups into the inclusion compound, thereby incorporating the inclusion compound into the membrane. (4) A compound containing a metal ion (e.g., a cerium salt) is reacted with a host compound in a solvent to form an inclusion compound, and then the inclusion compound or a solution thereof is added to a dispersion of a polymer electrolyte, and the resulting liquid is used to form a film by coating.

[0049] [Method of manufacturing membrane electrode assembly] The catalyst layer can be formed, for example, by the steps of preparing a catalyst ink (e.g., about 10% solids concentration) containing an electrode catalyst, an ionomer, and a solvent, applying the catalyst ink to the surface of a substrate and volatilizing the solvent in the coating to form a catalyst layer on the substrate surface, and transferring the catalyst layer on the substrate surface to an electrolyte membrane. The catalyst layer can also be formed by a method in which the catalyst ink is directly applied to a solid polymer electrolyte membrane instead of a substrate. A membrane electrode assembly can be produced by forming a cathode catalyst layer and an anode catalyst layer on the solid polymer electrolyte membrane.

[0050] Examples of methods for applying the catalyst ink include a spray method, a blade coating method using a doctor blade or an applicator, a die coating method, a reverse roll coater method, and an intermittent die coating method.

[0051] The anode catalyst layer may contain the metal ions and the host compound in a catalyst ink for forming the anode catalyst layer. Specifically, the catalyst ink for forming the anode catalyst layer may contain an electrode catalyst, an ionomer (e.g., an ionomer having a sulfonic acid group), the metal ions, a host compound, and a solvent. The metal ions and the host compound may be added separately or in the form of a complex of the two.

[0052] [Specific configurations of membrane electrode assembly and polymer electrolyte fuel cell] A solid polymer electrolyte fuel cell has as its basic unit a membrane electrode assembly (MEA) in which catalyst layers (electrodes) are bonded to both sides of a solid polymer electrolyte membrane. In a solid polymer electrolyte fuel cell, a gas diffusion layer is generally disposed on the outside of the catalyst layer. The gas diffusion layer is used to supply reactant gases and electrons to the catalyst layer, and is made of carbon paper, carbon cloth, or the like. The catalyst layer is the reaction site for the electrode reaction.

[0053] Hereinafter, the configuration of the membrane electrode assembly and the solid polymer fuel cell will be described with reference to FIG. 1. FIG. 1 is a schematic cross-sectional view for explaining a configuration example of the solid polymer fuel cell according to the present embodiment, and is a cross-sectional view of a main part of a fuel cell 10 as an example. The solid polymer fuel cell includes a stack of unit cells, each of which includes a power generation body and a fuel cell separator arranged on both sides of the power generation body. A plurality of unit cells are stacked in the stacking direction, and each unit cell is electrically connected in series. As shown in FIG. 1, the fuel cell 10 includes a plurality of unit cells 1, which are basic units, stacked. Each unit cell 1 is a solid polymer fuel cell that generates an electromotive force by an electrochemical reaction between an oxidant gas (e.g., air) and a fuel gas (e.g., hydrogen). The unit cell 1 includes a membrane electrode gas diffusion layer assembly (MEGA) 2 having gas diffusion layers (GDL: Gas Diffusion Layer) 7 arranged on both sides, and a separator 3 in contact with the MEGA 2 so as to partition the MEGA 2. In this embodiment, the MEGA 2 is sandwiched between a pair of separators 3, 3.

[0054] The MEGA2 includes a membrane electrode assembly (MEA) 4 and gas diffusion layers 7, 7 arranged on both sides of the MEA. The membrane electrode assembly 4 includes an electrolyte membrane 5 and a pair of electrodes 6, 6 joined to sandwich the electrolyte membrane 5. The electrolyte membrane 5 is, for example, a proton-conductive ion exchange membrane formed of a solid polymer material. The electrode 6 includes, for example, a porous carbon material carrying a catalyst such as platinum. The electrode 6 arranged on one side of the electrolyte membrane 5 functions as an anode, and the electrode 6 on the other side functions as a cathode. The gas diffusion layer 7 is formed of a conductive member having gas permeability. Examples of the conductive member having gas permeability include a carbon porous body such as carbon paper or carbon cloth, or a metal porous body such as a metal mesh or metal foam. In this embodiment, the anode electrode is formed of an anode catalyst layer, and the cathode electrode is formed of a cathode catalyst layer. EXAMPLES

[0055] The present embodiment will be described below using examples.

[0056] [Example 1] (Formation of cathode catalyst layer) A metal-supported catalyst as an electrode catalyst was dispersed in an ionomer solution (DE2020) containing water and ethanol using a bead mill to prepare a catalyst ink. The mass ratio of water to ethanol in the catalyst ink (water / ethanol) was approximately 1. The obtained catalyst ink was applied to a polytetrafluoroethylene sheet and dried to form a cathode catalyst layer.

[0057] The Pt coverage in the cathode catalyst layer is 0.2 mg / cm 2 The mass ratio of ionomer to carbon (I / C) was 1.0. As catalyst particles, 30% Pt / Vulcan (registered trademark) (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., TEC10V30E) was used.

[0058] (Formation of inclusion compounds (complexes)) 4'-Aminobenzo-15-crown-5-ether (also known as (benzo-15-crown-5)-4'-ylamine, TCI) (0.01 mol) was weighed out into a 100 mL recovery flask, ethanol (20 mL) and water (20 mL) were added, and the mixture was stirred at room temperature for 24 hours. After that, the solvent was removed using an evaporator, and the mixture was vacuum dried at 60°C for 1 hour to obtain a solid. It was confirmed by FT-IR that the peak derived from the ether group had shifted to the lower wavenumber side, confirming that the compound and Ce had formed an inclusion compound.

[0059] (Formation of anode catalyst layer) 60wt% Pt / Ketjen (registered trademark) was used as the electrode catalyst. The electrode catalyst and the above composite were dispersed in an ionomer solution (DE2020) containing water, ethanol, and Nafion (registered trademark) to prepare a catalyst ink. This catalyst ink was applied to a polytetrafluoroethylene sheet and dried to form an anode catalyst layer.

[0060] The Pt coverage of the anode catalyst layer is 0.1 mg / cm 2 , cerium ion concentration is 4 μg / cm 2 As described above, the host compound was contained in a molar ratio of Ce:host compound = 1:1. The mass ratio of ionomer to carbon (I / C) was 1.0.

[0061] (Fabrication of membrane electrode assembly) The obtained cathode catalyst layer and anode catalyst layer were thermally transferred onto both sides of a Nafion (registered trademark) membrane (NR211) to prepare a membrane electrode assembly E1. The thermal transfer conditions were 140° C. and 50 kgf / cm 2 (4.90 MPa) for 5 min. The electrode area of ​​the membrane electrode assembly for the initial performance test was 1 cm × 1 cm (1 cm 2 The electrode area of ​​the membrane electrode assembly for the durability test was 3.6 cm × 3.6 cm (12.96 cm 2 This membrane electrode assembly was sandwiched between paper diffusion layers (GDLs) with water-repellent layers to prepare a test cell.

[0062] [Example 2] A membrane / electrode assembly E2 was prepared in the same manner as in Example 1, except that 1-aza-18-crown-6-ether (also known as 1,4,7,10,13-pentaoxa-16-azacyclooctadecane, TCI) (0.01 mol) was used as the host compound.

[0063] [Example 3] A membrane electrode assembly E3 was produced in the same manner as in Example 1, except that 1-aza-1-methyl-18-crown-6-ether (0.01 mol) was used as the host compound. The 1-aza-1-methyl-18-crown-6-ether was synthesized by the following method.

[0064] In a three-neck flask equipped with a thermometer and a stirrer, 263 g (1 mol) of 1-aza-18-crown-6-ether and 75 g (2.5 mol) of formaldehyde were dissolved in 500 mL of methanol. To the resulting solution, 164 g (2 mol) of sodium acetate, 240 g (2 mol) of acetic acid, and 46.1 g (0.7 mol) of sodium cyanoborohydride were added, and the mixture was reacted for 2 hours at 25° C. while being purged with nitrogen by stirring. After the reaction was completed, a separation operation was performed to obtain 1-aza-1-methyl-18-crown-6-ether, which is an N-methylated product. 1 The compound was confirmed to have been obtained by H-NMR and MS.

[0065] [Example 4] A membrane / electrode assembly E4 was produced in the same manner as in Example 1, except that Cryptand222 (also known as 4,7,13,16,21,24-hexaoxa-1,10-diazabicyclo[8.8.8]hexacosane, TCI) (0.01 mol) was used as the host compound.

[0066] [Example 5] A membrane electrode assembly E5 was produced in the same manner as in Example 1, except that 1-aza-18-crown-6-ether nitrate (0.01 mol) was used as the host compound. The 1-aza-18-crown-6-ether nitrate was prepared by weighing out 1-aza-18-crown-6-ether and nitrate in a molar ratio of 1:1 in a 100 mL eggplant flask, adding it to a mixed solvent of ethanol and water, and stirring at room temperature for 24 hours. After that, the solvent was removed with an evaporator, and then vacuum drying was performed at 60°C for 1 hour to obtain the 1-aza-18-crown-6-ether nitrate.

[0067] [Example 6] A membrane electrode assembly E6 was produced in the same manner as in Example 1, except that the nitrate of 4'-aminobenzo-15-crown-5-ether (0.01 mol) was used as the host compound. The nitrate of 4'-aminobenzo-15-crown-5-ether was prepared by weighing 4'-aminobenzo-15-crown-5-ether and the nitrate in a molar ratio of 1:1 in a 100 mL eggplant flask, adding it to a mixed solvent of ethanol and water, and stirring it at room temperature for 24 hours. After that, the solvent was removed with an evaporator, and then vacuum drying was performed at 60°C for 1 hour to obtain the nitrate.

[0068] [Comparative Example 1] A membrane / electrode assembly C1 was produced in the same manner as in Example 1, except that no host compound was used.

[0069] [Comparative Example 2] A membrane / electrode assembly C2 was produced in the same manner as in Example 1, except that 18-crown-6-ether (also known as 1,4,7,10,13,16-hexaoxacyclooctadecane, TCI) (0.01 mol) was used as the host compound.

[0070] [evaluation] (Durability test: voltage drop rate) The above test cell (electrode area: 12.96 cm 2 ) was incorporated into a power generation cell and a durability test was conducted in a low humidity environment (90°C, 40% RH). The durability test was performed with the cell temperature at 90°C, hydrogen / air supplied, and a current density of 0.05 A / cm 2The initial characteristics of the polymer electrolyte fuel cell in this case and the characteristics after a durability test load were evaluated. Hydrogen and air were humidified and supplied to the cell so that the anode side had a dew point of 67°C and the cathode side had a dew point of 67°C, respectively, and the cell voltage at the beginning of operation and the relationship between the elapsed time after the start of operation and the cell voltage were measured. The results are shown in Table 1 below. In addition, under the above cell evaluation conditions, the cell voltage at the beginning of operation and the cell voltage 200 hours after the start of operation were measured.

[0071] (Productivity: Granularity) <Method of measuring particle size distribution> The particle size distribution of the catalyst ink was measured using a particle size distribution analyzer (MT3000II) manufactured by Microtrack Bell, and the D50 value was used. When the particle size distribution D50 (unit: μm) of the catalyst ink was 5 μm or less, it was rated as A, and when D50 was 6 to 10 μm, it was rated as B.

[0072] [Table 1]

[0073] The upper limit and / or lower limit of the numerical ranges described in this specification can be arbitrarily combined to define a preferred range. For example, the upper limit and lower limit of the numerical range can be arbitrarily combined to define a preferred range, the upper limit of the numerical range can be arbitrarily combined to define a preferred range, and the lower limit of the numerical range can be arbitrarily combined to define a preferred range.

[0074] Although the present embodiment has been described in detail above, the specific configuration is not limited to this embodiment, and even if there are design changes within the scope that does not deviate from the gist of this disclosure, they are included in this disclosure. [Explanation of symbols]

[0075] 1: cell, 2: MEGA (membrane electrode gas diffusion layer assembly), 3: separator (fuel cell separator), 4: membrane electrode assembly (MEA), 6: electrode, 7: gas diffusion layer, 10: fuel cell, 21, 22: gas flow path

Claims

1. A membrane electrode assembly having a solid polymer electrolyte membrane, an anode catalyst layer disposed on one surface of the solid polymer electrolyte membrane, and a cathode catalyst layer disposed on the other surface of the solid polymer electrolyte membrane, the membrane electrode assembly includes a metal ion selected from a cerium ion and a manganese ion, and a host compound capable of forming an inclusion compound with the metal ion, The host compound is a crown ether compound containing an amino group or a salt thereof.

2. 2. The membrane electrode assembly according to claim 1, wherein the host compound is a crown ether compound having an aromatic ring or an aliphatic ring substituted with an amino group, or a salt thereof.

3. The host compound is (—CH 2 -CH 2 -Y-) unit or (-CH 2 -CH 2 -CH 2 A crown ether compound or a salt thereof having a repeating structure of a crown ether unit having a repeating unit of a -Y-) unit (each Y is independently at least one selected from -O-, -NH-, and -NR-, at least one Y is selected from -NH- and -NR-, and each R is independently an alkyl group having 1 to 6 carbon atoms, and when two R are present, each R is a C alkyl group in which one or two carbon atoms may be substituted with an oxygen atom). 1 ~C 6 The membrane electrode assembly according to claim 1 , wherein the alkylene groups are each independently selected from the group consisting of aryl, aryl, aryl and heteroaryl.

4. The host compound is (—CH 2 -CH 2 -Y-) unit or (-CH 2 -CH 2 -CH 2 A crown ether compound or a salt thereof having a repeating structure of a crown ether unit having a repeating unit of -Y- (each Y is independently at least one selected from -O- and -NR-, at least one Y is selected from -NR-, each R is independently an alkyl group having 1 to 4 carbon atoms, and when two R are present, each R is an alkyl group having 1 to 4 carbon atoms, in which one or two carbon atoms may be substituted with an oxygen atom. 1 ~C 6 The membrane electrode assembly according to claim 1 , wherein the alkylene groups are each independently selected from the group consisting of aryl, aryl, aryl and heteroaryl.

5. 2. The membrane electrode assembly according to claim 1, wherein the salt of the crown ether compound containing an amino group is a nitrate, sulfate, carbonate, acetate, or propionate.

Citation Information

Patent Citations

  • Method for preparing CCM through direct coating of cathode and anode

    CN113299927A

  • High-durability organic antioxidant chelated cerium ion composite proton exchange membrane as well as preparation method and application thereof

    CN114276573A

  • Polymer electrolyte membrane and membrane electrode assembly for polymer electrolyte fuel cell

    JP2008130460A

  • Composite polymer electrolyte membrane, manufacturing method of the same, and manufacturing method of membrane electrode assembly

    JP2011222499A

  • Fluorine-containing ionomer composite material having ion exchange function, method for preparing the same, and use

    JP2013530279A